Author’s Neologisms as a Significant Style-Creating Component in the Novel “Yellow Prince” by Vasyl Barka (Linguostylistic Studies, 2021)
The article highlights the issue of individual author’s language creation process. The case study of the author's neologisms in the novel “Yellow Prince” by Vasyl Barka, has revealed that the writer actively introduces author's innovations into his artistic narrative. The neologisms created by the writer comprise noun, adjective, verb and adverb author's neologisms. The subject of the research is the author’s noun-neologisms. The goal is to characterize their semantics, creation-model, and features of functioning. In terms of the semantic-grammatical approach, all the authorial noun-neologisms of V. Barka are divided into three lexical-grammatical groups: names of persons, nouns with concrete-subject meaning, nouns with abstract meaning. The most numerous groups of noun innovations are names of persons and abstract names. Among the identified noun neo-lexemes denoting persons, most belong to the group of nouns that characterize people by activity, their inner world, the psychological state of the characters. Among the abstract noun neo-lexemes of V. Barka, the largest is the group of noun-names of actions, movements, processes. Innovations with a specific subject meaning, found in the novel “Yellow Prince”, often name the objects, household items, products; names of animals, plants, fruits; premises, buildings.All identified noun neo-lexemes are formed according to traditional word-forming models characteristic of the Ukrainian language. Productive ways of creating neo-lexemes are suffixation and word-building patterns. The vast majority of the author's noun-neologisms are stylistically loaded in the artistic discourse of Vasyl Barka. Author’s nominations often contain evaluative-expressive coloring in his works of art.The use of author’s neologisms testifies to the originality of the writer’s creative manner, the linguistic creativity of the author's linguistic personality. In the artistic text, innovations are an important aesthetic means of artistic representation.
Keywords: idiostyle; neo-lexeme; individual author’s nomination